Intestinal ganglioneuromatosis: an unusual aetiology for occult gastrointestinal bleeding. (30th September 2015) - Fernandes, Alexandra; Ferreira, Ana Margarida; Serra, Paula; Carvalho, Luís
Abstract : Intestinal ganglioneuromatosis is a rare disorder of the enteric nervous system. It is often associated with neurofibromatosis type 1 and multiple endocrine neoplasia type 2b but, more rarely, it can present in a sporadic and isolated form. A 66-year-old man presented with a 14-year history of iron deficiency anaemia, with no visible bleeding, requiring occasional blood transfusions. Haematological causes of anaemia were thoroughly excluded, and conventional endoscopic and radiological examinations showed no lesions. Capsule enteroscopy identified an ulcerated stenosis in the small bowel, but the biopsies taken at balloon enteroscopy were inconclusive. The patient underwent a laparotomy, which revealed a stiff and ulcerated stenosis in the ileum. Histological analysis demonstrated the presence of diffuse intestinal ganglioneuromatosis. Three years after surgery, the patient is asymptomatic, with normal haemoglobin levels. This case demonstrates an isolated form of intestinal ganglioneuromatosis, with an atypical presentation, difficult to diagnose despite an exhaustive evaluation.